Absorption of regional funds: a comparative analysis - Tosun, Jale (Journal of common market studies, 2014)
This article evaluates the determinants of the absorption performance of European Union Member States with regard to the European Regional Development Fund's (ERDF) 2000-06 programming period. Theoretically grounded in Europeanization research and studies of regional governance, the empirical analysis concentrates on the ERDF absorption performance of 25 Member States at the end of the programming period in 2008. The results of Tobit models show a positive relationship between ERDF absorption and government capacity. The estimation findings also demonstrate that new Member States generally had higher absorption rates than old Member States. Furthermore, Member States with high income levels were less likely to maximize the absorption of their ERDF allocations. Finally, there is some support for the hypothesis that fiscal decentralization has a negative impact on absorption performance.